2021
DOI: 10.1155/2021/3366870
|View full text |Cite
|
Sign up to set email alerts
|

Lee Silverman Voice Treatment to Improve Speech in Parkinson’s Disease: A Systemic Review and Meta-Analysis

Abstract: Background. Speech changes occur in the early stages of Parkinson’s disease (PD) and cause communication difficulties, leading to social isolation. Lee Silverman voice treatment (LSVT) is a speech therapy approach designed to improve patients’ language and voice capabilities. Objective. The effectiveness of the LSVT was compared with that of other speech interventions or no treatment to evaluate PD patients with dysarthria. Design. Systematic review with meta-analysis of randomized trials. Data Sources: PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This finding is critical given that disorders of speech and swallowing in PD result in significant decrements to health and quality of life but have also been found to be amenable to improvements with targeted SLP intervention. 13,14 In addition, recent work has identified that SLP services delivered via telehealth are feasible and efficacious in the treatment of Parkinson's disease. [15][16][17] In a recent study by Chan and colleagues, 17 intensive voice therapy sessions delivered over smartphone videoconferencing were perceived to be an equivalent alternative to traditional face-to-face in 70% of participants.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is critical given that disorders of speech and swallowing in PD result in significant decrements to health and quality of life but have also been found to be amenable to improvements with targeted SLP intervention. 13,14 In addition, recent work has identified that SLP services delivered via telehealth are feasible and efficacious in the treatment of Parkinson's disease. [15][16][17] In a recent study by Chan and colleagues, 17 intensive voice therapy sessions delivered over smartphone videoconferencing were perceived to be an equivalent alternative to traditional face-to-face in 70% of participants.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in airway‐protective treatment outcomes between the EMST and smTAP groups point to differences in the mechanistic targets of treatment (ie, strength‐ vs. skill‐based training), with EMST leading to greater improvements in MEP but smTAP resulting in greater improvements in voluntary and reflex cough function. The value of skill‐based training for individuals with PD is further supported by studies demonstrating improvement in speech and gait 49,50 . For the smTAP group, the improvements in voluntary and reflex cough function to levels indicative of improved airway clearance are of clear health impact, especially given that these individuals have dysphagia.…”
Section: Discussionmentioning
confidence: 96%
“…The value of skill-based training for individuals with PD is further supported by studies demonstrating improvement in speech and gait. 49,50 For the smTAP group, the improvements in voluntary and reflex cough function to levels indicative of improved airway clearance are of clear health impact, especially given that these individuals have dysphagia. This study supports the consideration of skillbased training approaches for cough rehabilitation in individuals with PD and dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analysis demonstrated the efficacy of the Lee Silverman Voice Treatment in increasing vocal loudness and functional communication among individuals with PD 69 . Speech language therapy (SLT) has potential benefits for PD dysphagia 70 .…”
Section: Parkinson Disease Rehabilitationmentioning
confidence: 99%